High NV density in a pink CVD diamond grown with N2O addition. (December 2020) - Tallaire, Alexandre; Brinza, Ovidiu; Huillery, Paul; Delord, Tom; Pellet-Mary, Clément; Staacke, Robert; Abel, Bernd; Pezzagna, Sébastien; Meijer, Jan; Touati, Nadia; Binet, Laurent; Ferrier, Alban; et al.
Abstract: Growing high-purity diamond containing dense negatively charged nitrogen-vacancy (NV − ) centre ensembles is desirable for the development of sensitive quantum sensors that explore the coherent manipulation of the spin states of this atomic-scale defect. By using N2 O as a dopant, we demonstrate that millimetre-thick single crystals can be grown by Chemical Vapour Deposition (CVD) with substitutional nitrogen concentrations as high as 26 ppm. With a high-energy electron irradiation treatment and in-situ annealing, up to 20% of this nitrogen can be successfully converted into NV − centres leading to densities of almost 5 ppm and to a crystal displaying pink colouration and appealing optical properties. The longitudinal relaxation T1 time in such a highly doped diamond is measured to be around 3.5 ms at 300 K while inhomogeneous dephasing time T2 ∗ is estimated to 600 ns. Despite the high NV density, Electron Spin Resonance lines are resolved with clear hyperfine splitting induced by the nuclear spin of nitrogen. The dependence of T1 on the orientation of the magnetic field suggests that relaxation is dominated by NV-NV dipole interactions when no magnetic field is applied. Such engineered crystals constitute a promising platform for developing future quantum sensing applications. Graphical abstract: Image 1 Highlights: Millimetre thick diamond single crystals with addition of 500 ppm of N2 O. Substitutional nitrogen conversion into NV centres by electron irradiation and in situ annealing with 20% efficiency. High total NV density of 7 ppm (NV − of 4.6 ppm) leading to pink colouration. Long T2 ∗ coherence time of 600 ns in irradiated samples. High [NV − ] × T2 ∗ products of 3 μs ppm.